Victory - Cooper, Susan, 1935- (NY : Aladdin Paperbacks, 2006)
Alternating chapters follow the mysterious connection between a homesick English girl living in present-day America and an eleven-year-old boy serving in the British Royal Navy in 1803, aboard the H.M.S. Victory, commanded by Admiral Horatio Nelson.
A Junior Library Guild selection.
Keywords: Victory (Man of war) -- Juvenile fiction; Victory (Man of war) -- Fiction; Sea stories; Sea stories; Great Britain -- History, Naval -- 19th century -- Juvenile fiction; Great Britain -- History, Naval -- 19th century -- Fiction; Sea stories